'Environments of concern': reframing challenging behaviour within a human rights approach. (2nd January 2023) - Jorgensen, Mikaela; Nankervis, Karen; Chan, Jeffrey
Abstract : While disability is recognised by the United Nations Convention on the Rights of Persons with Disabilities (CRPD) as an evolving concept, the language of positive behaviour support has not kept pace with the current human rights-based approach. The widely-used terms 'challenging behaviour' and 'behaviours that challenge' imply that the behaviour is inherent in a person with disability. Words have power in shaping practice: when the behaviour of the person with disability is framed as the problem, this leads to a pathologisation or labelling that can provide a rationale to medicate and restrain as a way of 'managing the challenging behaviour'. Many behaviours seen as being challenging could be better understood as 'adaptive behaviours to maladaptive environments', or legitimate responses to difficult environments and situations. In this paper, we argue that the language and implementation of positive behaviour support should better take into account the CRPD and contemporary evidence on behaviour change interventions, which support a shift away from focusing on individuals' behaviours towards putting environments front and centre. We outline how the social-ecological model could be used as a framework to more explicitly address 'environments of concern' in developing tailored and system-wide responses to behaviour support needs. We argue there is an urgency for this paradigm shift to better reflect the views of people with disability and improve outcomes.